Students of SD Negeri 2 Cikancas with a Focus on Agility in Traditional Sports Games and Blocking Numbersrts Games and Blocking Numbers - Adipradana, Ronggur A; Nurdiansyah, Dani (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
In traditional sports, agility is very necessary, especially in the blocking number. Because, agility is very important and is the key to the blocking number to maintain balance and coordination. Objective . The objective of this study was to determine the effect of ladder drill training on increasing agility in traditional sports games in the hurdles category. Materials and Methods. The method in this study is a type of quantitative research using an experimental method with a one group pretest-post test design. The instruments used were the pretest and posttest of Zig-Zag agility using 5 cones , non-slip surfaces , and a stopwatch. The data analysis technique used was the prerequisite analysis test, namely: 1) normality test, 2) homogeneity test and 3) hypothesis test. This study was conducted at SD Negeri 2 Cikancas with a sample of 15 fifth grade students, who were selected using the purposive sampling technique. Results. The results of this study indicate that ladder drill training has a significant effect on agility in blocking players, namely grade V students of SDN 2 Cikancas, based on the t-test (pired sample t-test), the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected because the significance value (2-tailed) is 0.000>0.05 of 7.190 or can be interpreted as (7.190>1.761). Conclusion. Based on the results of the research that have been described previously, it can be concluded that this research has a significant influence on agility.